People with physical disabilities in Sri Lanka are in need for the service of community physiotherapists - Senadheera, Vindya Vimani; Malwanage, Kavinda Tharani; Mayooran, Sithravelayuthan; Rikas, Abdul Majeed Mohomad; Prasanna, Agampodi Liyanage Indrajith (International Journal Of Community Medicine And Public Health, 2021)
Background: Physiotherapists have long been recognized as important providers of services for people with disability. In Sri Lanka the concept of community physiotherapy has not emerged yet. The present study aimed to identify the need for ‘community physiotherapy service’ in Kandy district, Sri Lanka. Methods: A community service projection community based rehabilitation, of three years was conducted by the department of physiotherapy, faculty of allied health sciences, University of Peradeniya, Sri Lanka in 2017-2019 in collaboration with department of social service and social welfare of Kandy district secretariat, Sri Lanka. Results: One hundred and seventy participants with physical disabilities were included in the study 94 (55.29%) were males (mean age; 33.57 (SD ±23.17) and 76 (44.71%) were females (mean age; 33.14 (SD ±24.98). The pediatric population was 41.76% (N=71) followed by 38.82% of adults (N=66) and 19.41% of elderly patients (N=33) of the total population. The highest number of PWD had pediatric conditions (39.41%), followed by musculoskeletal (31.76%), neurological (15.88%), geriatric (8.82%) and cardio-respiratory (4.12%) conditions. The majority (55.88%) of all the people with disabilities who visited the clinics were in need for further physiotherapy consultation and follow up. Conclusions: In Kandy district of Sri Lanka alone, number of people with physical disabilities who are in need of continuous physiotherapy follow ups is high compared to services already available. Conducting a successful community-based rehabilitation program in Sri Lanka as a whole, require having a specialized health care practitioner to the primary health care team; ‘a community physiotherapist’.